The development of a new SOFI model for performance management of medium-sized and large companies - Kovačević, Biljana (Decision Making: Applications in Management and Engineering, 2023)
Measurement and adequate performance management of a company represent an imperative regarding the attainment of competitive advantage in the market. This need is especially pronounced in medium-sized and large companies, which represent complex organizations and require the application of scientific principles for solving complex issues in practice. Therefore, the performance management process in medium-sized and large companies is singled out as the subject of the research. It is important to point out that the main concept of the paper is the macro aspect of the performance management process. The primary goal of the research is the development of a new model for performance management based on considering all important parameters of business operations of these companies on the territory of the Republic of Srpska. The research was conducted via combined methods – a multiple case study which implies four companies and a survey questionnaire. Through the analysis of many models in the literature, seven were singled out which were studied further. The main elements and conceptual bases of these models served as the basis for conducting research and creating a new model for performance management. The result of the published research represents “SOFI” model (strategic, organizational, financial and information–technological aspects), whose application contributes towards easier management by managers, as well as making correct management decisions in the conditions of uncertainty.